2009
DOI: 10.1007/s00508-008-1127-x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile: a new zoonotic agent?

Abstract: Clostridium difficile is mainly considered a nosocomial pathogen associated with diarrhea and pseudomembranous colitis in hospitalized patients. Austrian hospitals reported 2761 cases of C. difficile infection (including 277 lethal outcomes) in 2007, compared with 777 cases (including 54 lethal outcomes) in 2003. The occurrence of community-acquired C. difficile infection is also increasingly reported. Recent studies have shown the occurrence of C. difficile in food and animals. The aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 47 publications
8
47
2
4
Order By: Relevance
“…The places where C. difficile was isolated are places of high animal traffic and rough floor (spores persist in cracks) with more likelihood of faecal contamination (Weese et al, 2000). Similar type of ribotype was reported from various species like in piglets (Keessen et al, 2013), calves (Costa et al, 2011), humans (Debast et al, 2009) and other food animals (Indra et al, 2009) and also in meat implicated in outbreaks (Rodriguez-Palacios et al, 2009). This paved way for making an assumption that C. difficile transmission from animals to human is likely to occur.…”
Section: Clostridium Difficilementioning
confidence: 60%
See 1 more Smart Citation
“…The places where C. difficile was isolated are places of high animal traffic and rough floor (spores persist in cracks) with more likelihood of faecal contamination (Weese et al, 2000). Similar type of ribotype was reported from various species like in piglets (Keessen et al, 2013), calves (Costa et al, 2011), humans (Debast et al, 2009) and other food animals (Indra et al, 2009) and also in meat implicated in outbreaks (Rodriguez-Palacios et al, 2009). This paved way for making an assumption that C. difficile transmission from animals to human is likely to occur.…”
Section: Clostridium Difficilementioning
confidence: 60%
“…This paved way for making an assumption that C. difficile transmission from animals to human is likely to occur. An Austrian study concluded that animal reservoirs can be a possible source for human CDI infection through the food animals (Indra et al, 2009). However frank zoonosis was not established, owing to the ubiquitous nature of the organism it may act as common source for both animals and human beings.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…C. difficile is widely recognized as a commensal and enteric pathogen in a wide range of host species (178)(179)(180). To date, C. difficile been recovered from numerous animal sources, including livestock (pigs, piglets, cows, calves, sheep, lambs, goats, and chickens), domestic animals (cats and dogs), equines (horses and foals), wildlife (rabbits, wild birds, shrews, raccoons, feral swine, ostriches, Kodiak bears, zebras, kangaroos, elephants, ibex, tamarin monkeys, and chimpanzees), and marine organisms (bivalve molluscs) (103,178,(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196). Many of these studies described differences in prevalence (particularly a decline with age), toxigenic status, antibiotic resistance, clonal lineage, and host susceptibility to disease, as well as differences in veterinary and agricultural practices (178,180).…”
Section: Animal Reservoirs and Zoonotic Potentialmentioning
confidence: 99%
“…The isolates were not classified as to toxinotype or ribotype, but were positive for both toxins A and B. In a study in Austria, zero out of 84 meat samples (51 beef, 27 pork, 6 chicken) were positive for C. difficile 7 ; whereas, in another Austrian study, 3 out of 100 (3%) were positive for C. difficile.…”
mentioning
confidence: 92%